Pardon, parole, and remission: the inmates’s second chance - Ahmad Fuzi, Fauziah Hani; Kamarudin, Abdul Rani; Zainal Abidin, Muhammad ‘Azzam (2018)
For the convicted offenders who were not given fine or bond of good behaviour, they would end up in prison. Spending time behind the iron bar characterizes rigid disciplines, provision of bare necessities, strict security arrangement, and monotonous routine life. Despite the Prison Department having rehabilitative programs designed to reform the prisoners from a criminal to an honest life hence reducing his propensity to commit crimes, the fact that imprisonment sentence, especially for a long period, invites other problems too such as prison overcrowding, criminogenic exposure, and unnecessary spending of public fund for the expenditure of the criminals. Thus, to solve these problems and to promote good behaviour of the prisoners while in custody, the authorities introduced Pardon, Parole, and Remission Systems. These systems aim at giving the prisoners a second chance in the sense that they have their incarceration period significantly shortened. The objectives and effects of these systems are about the same i.e. to maintain the offenders’ relation with their families and community as an agent of reform, to reduce the problem of prison overcrowding, and to save the public fund. However, Pardon, Parole, and Remission are relatively not understood by the public on how they interchangeably function as they are rarely publicised. Due to the lack of understanding, it is open wide to loads of criticisms and questions on the validity of the decisions made by the authorities in respect of these three systems especially when it involves politicians. Therefore, this qualitative based research paper, discusses these three systems and how they differ in terms of application with reference to relevant statutes, decided cases, and media sources. At the end, this paper shows that in the eye of the law, everybody deserves a second chance no matter who he is in that the offender will be returning to his society.